1990
DOI: 10.1017/s0022112090003469
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of the turbulent spot in a laminar boundary layer with a favourable pressure gradient

Abstract: The evolution of a turbulent spot in an accelerating laminar boundary-layer flow was investigated. The type of boundary layer chosen for this experiment resembles in every respect the flow in the vicinity of a stagnation point theoretically described by Falkner and Skan. The rate of growth of the spot was significantly inhibited by the favourable pressure gradient in all three directions. It became much shorter and narrower in comparison with a similar spot generated in a Blasius boundary layer at comparable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 15 publications
5
40
0
2
Order By: Relevance
“…With favorable pressure gradient the laminar velocity profile is fuller leading to a reduced ⌬u m . Hence the growth rate of the spot is reduced, consistent with Katz et al 10 ͑ii͒ In an adverse pressure gradient flow, following the same argument, ⌬u increases due to the deceleration of the laminar base flow and an enhanced spot spreading can be obtained, consistent with was reduced during spot merging into a full-turbulent boundary layer downstream. In this case the surrounding fluid u l ͑y͒ changes to turbulent and ⌬u m reduces, ultimately to zero, leaving normal turbulent diffusion, rather than enhanced lateral growth as the main mechanism.…”
Section: Lateral Spreading Mechanismsupporting
confidence: 83%
See 1 more Smart Citation
“…With favorable pressure gradient the laminar velocity profile is fuller leading to a reduced ⌬u m . Hence the growth rate of the spot is reduced, consistent with Katz et al 10 ͑ii͒ In an adverse pressure gradient flow, following the same argument, ⌬u increases due to the deceleration of the laminar base flow and an enhanced spot spreading can be obtained, consistent with was reduced during spot merging into a full-turbulent boundary layer downstream. In this case the surrounding fluid u l ͑y͒ changes to turbulent and ⌬u m reduces, ultimately to zero, leaving normal turbulent diffusion, rather than enhanced lateral growth as the main mechanism.…”
Section: Lateral Spreading Mechanismsupporting
confidence: 83%
“…This has been confirmed in later work, including Katz et al 10 for a favorable pressure gradient boundary layer and Seifert and Wygnanski, 7 who found a doubling of spot growth rate in a strong adverse pressure gradient flow. Measurements based on surface heat transfer Zhong et al 11 also showed a significant increase in spot lateral spreading rates with increasing adverse pressure gradients, although the growth angles measured in this way are smaller than those based on velocity measurements.…”
Section: Introductionsupporting
confidence: 57%
“…The first such study was conducted by Wygnanski [8] who determined that, in a favourable pressure gradient, neither the leading nor the trailing-edge convection rate of the turbulent spot scaled directly with the freestream velocity. This result was later expanded upon by Katz et al [9], who studied a turbulent spot developing in a boundary layer accelerating in a pressure gradient which Could be described by the Falkner-Skan parameter fl = 1. They showed that, under these conditions, the leading-and trailing-edge convection velocities of the spot increased as the square root of distance from the spot origin, while the freestream velocity increased linearly with the same length.…”
Section: Introductionmentioning
confidence: 83%
“…For incompressible flow with zero-pressure-gradient, the lateral spreading angle is approximately 10 degrees (Schubauer & Klebanoff, 1956). Many other characteristics of turbulent spots in incompressible (low-speed) flows have been well documented in the literature (see, Wygnanski et al, 1979;Katz et al, 1982;Gad-el Hak et al, 1981;Glezer et al, 1989;Seifert & Wygnanski, 1995). The lateral spreading or growth of the turbulent spot strongly depends on the Mach number.…”
Section: Scope Of Present Researchmentioning
confidence: 99%